Mehboob...India's DeMille : The First Biography - Reuben, Bunny (New Delhi HarperCollins Publishers, 1994)
Biography of Mehboob Khan, 1906-1964, Indian film-maker.
Include Illustrations
Keywords: Motion picture producers and directors -- India -- Biography